Pengaruh Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Hasil Belajar Siswa - Agus Maramba Meha; Yusni W Mbau; Yonatan Foeh (Magister Pendidikan Biologi, Universitas Negeri Medan, 2020)
The problem in this study is the low learning outcomes of class VII students of SMP Negeri 20 Kupang. This study aims to determine the effect of the Make A Match type of cooperative learning model on learning outcomes. The experimental research method used is the Posttest-Only Control Group Design. The population of class VII students was 253 students and the sample of class VIID and class VIIH was 54 students. Data collection using learning outcomes tests. Analyzed using t-test, assisted by SPSS For Windows version 23. Hypothesis test results obtained tcount 8,194> 2,00665 ttable at 0,000 significance or less than 0.05, indicating that there are differences in student learning outcomes between the control and experimental classes. It is shown by increasing students' understanding of the digestive system material, students look very enthusiastic in learning, have curiosity, and dare to express opinions during the learning process. Therefore, the Make A Match learning model has great potential in developing students' ideas on problem-solving in learning, as evidenced by the high percentage of student learning outcomes, namely C1 93.055%, C2 75.462%, and C3 73.765%.